Percepção ambiental e uso de parques urbanos por frequentadores do parque jardim da conquista, São Paulo/SP - Régis, Milena de Moura (2016)
Comprehending the environmental perception allows the understanding of how happens the relationbetween human being and environment, and from this knowledge we obtain subsidies to create conservation policies, and for the decision taking about management strategies of public green areas, like urban parks. It is from this perspective, that this study have identified the environmental perception and use of urban parks by regulars of Jardim da Conquista Park (JCP), besides having identified the environmental perception of the frequenters of Jardim da Conquista Park about the JCP. In order to do it, 204 Park goers have been interviewed, of these, 127(62,25%) were women and 77 (37,75%) were men. And the research was divided in two phases, the first called: “Environmental Perception of Urban Parks”; and the second called: “Environmental Perception of Jardim da Conquista Park”. In the first phase, it was identified how the interviewed goers of Jardim da Conquista Park realize and use urban parks. For this, it was adopted the factor analysis statistical technique, that have indicated four categories representig the environmental perception of the interviewed about use and functions of urban parks. The identified categories are: 1.Social Function of Urban Parks; 2.Environmental Services of Urban Parks; 3.Infrastructure and use of Urban Parks; and 4.Conservation of Urban Nature. Such aspects have allowed the researcher to identify the important criteria to goers, when choosing which park model they wish to visit. Hence, the categories have been crossed with some variables used to feature the interviewed profile, those are: genre; age; marital status; and having children or not. Relating the respondent profile, with identified categories, have enabled to conclude that different observed groups, realize and use urban parks in similar ways. In the second phase, it was identified how the interviewed goers of Jardim da Conquista Park realize and use the JCP. In this regard, were observed variables that addressed aspects about the infrastructure, services, and available equipaments in the Park. Besides analyzing one open question, that have allowed to identify how the interviewed realizes and uses the JCP, through the content analysis technique. The quantitative data analysis, in this phase of the research, have demonstrated that the interviewed evaluate positively the Jardim da Conquista Park in relation to the observed aspects, indicating that these individuals realize and use the JCP, as a leisure and recreation space, that offers good equipments for the achievement of these and other activities. The qualitative data analysis, have also demonstrated (through the categories: welfare; evaluation/maintenance; and use, assigned to the JPC, from the analysis of the interviewed´s discourse), that the studied population positively relates to this place. However, the studied population have also indicated aspects to be improved in the JCP, those are: the drinking fountains availability; fitness equipaments availability; parking slots, and others. Despite it, in this phase of the study, we conclude that the interviewed realize and use the JCP, as a cozy and nice place, where it is possible to interact with other people and also practice leisure and recreation activites, in addition to characterize the JCP as a familiar environment.